ANALISIS STRATEGIC FLEXIBILITY DAN PENERAPAN STANDAR EURO 2 TERHADAP PENGEMBANGAN PRODUK: STUDI KASUS PT. PANTJA MOTOR-ATPM ISUZU - Herman, Robertus Tang; Manggala, Muh. Panji; Sutjiadi, Adrianto; Yusuf, Ahmad Mukhlis (Bina Nusantara University, 2008)
During the tight competition in automotive market in Indonesia, all car producers are demanded to adopt a competitive strategy to retain or to enlarge their market shares. In Indonesia, the size of the car market has been steadily decreased since 2006, commercial cars sales decreases by 60 percent. Premium car sales go down by 40 percent. (Gaikindo, 2006) While some players in the automotive industry is still optimistic, the opposite view happens with Isuzu producer. The problem is not only decreasing national cars issue but also the release of a regulation regarding standardization of vehicle emission. This regulation states that Euro 2 standardization will be applied starting January 2005 for new vehicles, and for existing cars, it will be starting in January 2007. Isuzu may change all its product line up, especially concerning for their product development to align with government rules about Euro 2 standardization, however, this moves will affect for sale price, new product investment and consumer preferences. The problem that facing Isuzu is that how to compete in the middle of decreasing cars sales and how flexible the strategy is in its implementation and what decisions should be taken regarding the Minister Environments Decision about gas emission from so that the company still can survive and compete in market by providing quality services for the consumer. This study also provides some recommendations to face the aforementioned matters above.